Dialectics of Religion and Culture: Socio-Anthropological Study of Islam in The Sasak Tribe Society - Lalu Muhammad Ridho Firmansyah; Faizal Efendi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
This article explains about the religion as the guidance for the people who live in this world that has cultural value in themselves. The human has the culture as creatures, ethics and feelings in conducting the interaction with the God, the other people, and with the nature. Religion and culture have been united in social-religion life in Indonesia. This study ahs purpose to describe the dialectical relation between Islam and local culture in Sasak ethnic that exist in Lombok island by using strategy approach socio-anthropology. This study will elaborate on dialectical Islam and culture and the practicality of religion and culture as the contextual that based on the customs as the effort as maintenance the great value to align the religion life moderatly based on the value of faith that has been as the mutual agreement.